Interaction of Scenedesmus quadricauda and native bacteria in marine biopharmaceutical wastewater for desirable lipid production and wastewater treatment. (February 2023) - Chen, Junren; Ren, Zian; Li, Zheng; Wang, Bo; Qi, Yuejun; Yan, Wenbao; Liu, Qingqing; Song, Hengyu; Han, Qingxiang; Zhang, Lijie
Abstract: Improving knowledge of the alga–bacterium interaction can promote the wastewater treatment. The untreated marine biopharmaceutical wastewater (containing native bacteria) was used directly for culturing microalgae. Unlike previous studies on specific bacteria in algal–bacterial co-culture systems, the effect of native bacteria in wastewater on microalgae growth was investigated in this study. The results showed that the coexistence of native bacteria greatly promoted the microalgae growth, ultimately producing biomass of 0.64 g/L and biomass productivity of 56.18 mg/L·d. Moreover, the lipid accumulation in the algae + bacteria group was 1.31 and 1.13 times higher than those of BG11 and pure algae, respectively, mainly attributed to the fact that bacteria provided a good environment for microalgae growth by using extracellular substances released from microalgae for their own growth, and providing micromolecules of organic matter and other required elements to microalgae. This study would lay the theoretical foundation for improving biopharmaceutical wastewater treatment. Graphical abstract: Image 1 Highlights: Microalgae was introduced to real marine biopharmaceutical wastewater. Alga–bacterium interaction improved the algal growth to 0.64 g/L of biomass. The lipid accumulation of microalgae in co-culture was improved. Pollutant removal was enhanced in co-culture due to the bacterial community. Algal–bacterial interaction mechanism in real wastewater was revealed.